Mathematics: applications and connections, course 3 - Collins, William and othres (New York : Glencoe / McGrow-Hill, 1998)
Mathematics and Statistics
Keywords: Mathematics; Algebra; Statistics and data analysis; Geometry; Patterns and number sense; Real numbers; Ratio and proportion; Probabikity